Implementasi Program Asistensi Mengajar Berbasis Mikrokontroler dalam Pembelajaran Fisika untuk Meningkatkan Kecakapan Digital Siswa Kelas XII - Violin, Friskha Mauranessa; Rahmawati, Indah Anggun; Khoirunnisa, Khoirunnisa; Nafi’an, Nabiel Auli Ilma; Riza, Nabila Asyfa (JPM: Jurnal Pengabdian Masyarakat, 2026)
The teaching assistance program at SMAN 1 Karanganom was implemented to address the low integration of digital technology in physics learning, particularly in digital instruments and microcontroller topics. This program aimed to enhance the digital competence of Grade XII students through concept and practice-based learning using the Jigsaw and Project-Based Learning (PjBL) models, emphasizing student-centered and collaborative activities. The program was conducted over four weeks and involved students from classes XII H, XII I, XII J, and XII K as the primary participants, in collaboration with physics teachers and the school management at SMAN 1 Karanganom. The activity stages included instruction on digital instrument concepts, an introduction to Arduino-based microcontrollers, and the development of simple automation projects. Data were collected through pretest-posttest, digital competence questionnaires, and classroom observations. The results showed improvements in students’ conceptual understanding and technical skills. The average posttest scores increased compared to the pretest results, with normalized gain (N-gain) values ranging from 0.05 to 0.47, indicating low to moderate improvement levels. Furthermore, the final questionnaire results revealed an increase in students’ digital competence, with more than 70% of students categorized as “good” and “very good” in aspects of logic gate understanding, digital input-output system, and microcontroller programming. Project-based learning also promoted higher levels of student engagement, collaboration, and positive attitudes toward digital technology. Therefore, this teaching assistance program was effective in improving students’ digital competence and can serve as a contextual, practical, and relevant alternative approach to physics learning aligned with 21st-century demands.